Ecological Water Quality and Management at a River Basin Level: A Case Study from River Basin Kosynthos in June 2011 - Ntislidou, Ch.; Basdeki, A.; Papacharalampou, Ch.; Albanakis, K.; Lazaridou, M.; Voudouris, K. (IntechOpen, 2012)
None